An Empirical Analysis on the Impact of Tax Policy on the Chinese Listed Companies’ Capital Structure - Zhou, Xiang (2013)
This paper will adopt GMM estimation method to analyze how the tax factors affect Chinese listed companies’ capital structure. In addition, this paper reviews the previous studies about capital structure theory and the main findings of firm’s financing behaviors in Chinese market. Based on these previous researches, it analyzes the current situation of capital structure of firms in China. Then In empirical analysis, this paper uses the panel data of Chinese listed companies from 2007-2012 to run a regression model to find the impact of the tax rate on capital structure. Finally, this paper theoretically analyzes the influence of tax on the capital structure and will reason out the cost of stock financing for listed companies is lower under the current tax system in China. In other words, firms have little incentive to use debt financing. The results also found that a feature of the tax has a little impact on the company’s leverage. It also provides an important new evidence for the view of Graham (2008)” tax has an impact on the company’s financial decisions, but the influence is little”, and the China's capital market is presented a feature of "low in debt and prefer equity financing".